KORELASI ANTARA RASIO NEUTROFIL LIMFOSIT DENGAN VOLUME INFARK SEREBRI PADA PENDERITA STROKE ISKEMIK AKUT - Ilsa Hunaifi,* Triana Dyah Cahyawati** (NEURONA, 2019)
INTRODUCTION INFLAMMATION PLAYS A KEY ROLE IN STROKE PATHOPHYSIOLOGY NEUTROPHILS IS ONE OF THE EARLIEST LEUCOCYTE SUBTYPES TO INFILTRATE THE ISCHEMIA AREA OF THE BRAIN THE NEUTROPHILLYMPHOCYTE RATIO NLR IS INDEPENDENT OF THE SEVERITY OF CORONARY HEART DISEASE AND AS A PREDICTOR OF POOR CLINICAL OUTCOMES IN PATIENTS WITH CORONARY HEART DISEASE UNDERGOING ANGIOGRAPHY THE NEUTROPHILLYMPHOCYTE RATIO VALUES MAY BE A PROGNOSTIC FACTOR IN ISCHEMIC STROKE PATIENTS THE NEUTROPHIL LYMPHOCYTE RATIO VALUES CAN ALSO BE USED IN PREDICTING INFARCT SIZE HOWEVER LIMITED STUDY HAS BEEN CONDUCTED IN THIS AREA